2013
DOI: 10.4236/ojmp.2013.21005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Caregiving and Metabolic Syndrome with Perceived Decline in Cognitive Function 8 Years Later: A Pilot Study Suggesting Important Avenues for Future Research

Abstract: The chronic stress of caregiving has been associated with increased risk for cognitive decline and dementia. One theoretical model suggests that a group of risk factors known as the metabolic syndrome MET_SYN (e.g. hypertension, poor glucose regulation, central obesity, and high triglyceride levels) that have demonstrated associations with both stress and cognitive decline, may mediate the association between caregiver stress and cognitive decline. It is also possible that caregiving may moderate the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Prior research has suggested that during earlier stages of cognitive decline, subtle memory complaints may not have a functional impact, although it has been reported that poor results obtained in MFE-30 may be an indicator of future development of dementia [37,47]. Many studies directed to analyze the impact of caregiving on cognition have focused on the effects of taking care of people with dementia suggesting that caregivers display greater vulnerability to cognitive decline [32,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has suggested that during earlier stages of cognitive decline, subtle memory complaints may not have a functional impact, although it has been reported that poor results obtained in MFE-30 may be an indicator of future development of dementia [37,47]. Many studies directed to analyze the impact of caregiving on cognition have focused on the effects of taking care of people with dementia suggesting that caregivers display greater vulnerability to cognitive decline [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration associated with the caring task could be manifested as an impairment of memory (both immediate and delayed), reduced verbal fluency, vocabulary and executive functions decline [5,29] and, in some subjects, as an increased risk of developing dementia [30,31]. In fact, different studies have shown that caregivers of people with dementia are more vulnerable to suffer cognitive impairment [30,32,33]. Physical consequences and fatigue can influence cognitive abilities such as concentration, which is remarkably decreased in caregivers [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, there have been dozens of studies examining the adverse effects of dementia caregiving on physiological biomarkers as well as markers of hypothalamic-pituitary axis activity, immune function, and cellular aging [20 && ]. Caregiving has been linked to development of mood Condition-specific symptoms at night, e.g., leg cramps or hallucinations in Parkinson's disease and substance use disorders, metabolic syndrome (hypertension, poor glucose regulation, central obesity, and high triglyceride levels), heart disease, arthritis, and chronic back pain [21][22][23]. Household members of persons with dementia have more medical service utilization and greater healthcare costs than those living with persons without dementia [24].…”
Section: Health and Functional Consequences Of Insomniamentioning
confidence: 99%
“…One of the most compelling recent contributions to the literature on caregiver outcomes is the connection between caregiving and caregivers' risk for dementia (Brummett, Austin, Welsh-Bohmer, Williams, & Siegler, 2013;Gouin et al, 2016;Rickenbach, Almeida, Seeman, & Lachman, 2014;Vitaliano, Murphy, Young, Echeverria, & Borson, 2011). Stress and depression levels that typically are associated with dementia caregiving have been found to influence several regions of the brain (Diamond & Kim, 2002;Roozendaal, McReynolds, & McGaugh, 2004) and cognitive dysfunction (Bremner, 1999;Levy, Dachir, Arbel, & Kadar, 1994).…”
Section: Caregiver Outcomesmentioning
confidence: 99%